2004
DOI: 10.1095/biolreprod.104.027961
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Physiology and Development of Artificial Insemination Technology in Killer Whales (Orcinus orca)1

Abstract: Research was conducted to define the basic reproductive physiology of killer whales (Orcinus orca) and to use this knowledge to facilitate the development of artificial insemination procedures. The specific objectives were 1) to determine the excretory dynamics of urinary LH and ovarian steroid metabolites during the estrous cycle; 2) to evaluate the effect of an exogenously administered, synthetic progesterone analog on reproductive hormone excretion; 3) to validate the use of transabdominal ultrasound for ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 39 publications
4
63
1
5
Order By: Relevance
“…There appears to be a strong relationship between urine progesterone and PDG, suggesting a relatively simple, though crude, transformation that links the 2 values (Stanczyk et al 1997, Falk et al 1999. The urine progesterone values were similar to other mammals (Herrick et al 2000, Khan et al 2008) and comparable to the transformed PDG values reported in other cetaceans (Robeck et al 2004(Robeck et al , 2005. Urine data was available for only 2 demographic groups in the present study: immature males and immature females.…”
Section: Urine Progesteronesupporting
confidence: 86%
See 1 more Smart Citation
“…There appears to be a strong relationship between urine progesterone and PDG, suggesting a relatively simple, though crude, transformation that links the 2 values (Stanczyk et al 1997, Falk et al 1999. The urine progesterone values were similar to other mammals (Herrick et al 2000, Khan et al 2008) and comparable to the transformed PDG values reported in other cetaceans (Robeck et al 2004(Robeck et al , 2005. Urine data was available for only 2 demographic groups in the present study: immature males and immature females.…”
Section: Urine Progesteronesupporting
confidence: 86%
“…Though urine levels of progesterone have not been reported previously in any cetacean, the progesterone metabolite, pregnanediol-3 alpha-glucuronide (PDG), has been measured in several odontocete species (Walker et al 1988, Kjeld 2001, Robeck et al 2004). There appears to be a strong relationship between urine progesterone and PDG, suggesting a relatively simple, though crude, transformation that links the 2 values (Stanczyk et al 1997, Falk et al 1999.…”
Section: Urine Progesteronementioning
confidence: 99%
“…Serum and urine were collected during spontaneous and GnRH-induced LH surges, which were clearly identified in serum, but not in urine. By contrast, this antibody has proven effective in measuring LH concentrations in urine of other species, including callitrichids (Ziegler et al, 1993(Ziegler et al, , 1996, bottlenose and white-sided dolphins (Robeck et al, 2005), killer whales (Robeck et al, 2004), giant pandas (Kersey, Monfort, Brown, unpubl. ), manatees (Iske, Brown, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol itself did not interfere with antigen/antibody binding, as determined by similar parallelism and mass recovery analyses of samples spiked with exogenous hormone standards to results from samples without glycerol. Many studies have evaluated urinary protein hormones, like LH and prolactin, often using neat urine (e.g., Czekala et al, 1988;French et al, 1992French et al, , 1999Ziegler et al, 1993;Miller and Soules, 1996;Robeck et al, 2004Robeck et al, , 2005. However, when no immunoactivity was observed in neat samples, either in longitudinal samples or as a result of parallelism tests on urine pools, efforts were made to concentrate samples to ensure the problem was not due to sample dilution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation